Adopting and adapting an Internet intervention to support breastfeeding duration and breastfeeding research throughout regional Western Australia - Giglia, Roslyn; Binns, Colin (National Rural Health Alliance, 2011)
Adopting and adapting an Internet intervention to support breastfeeding duration and breastfeeding research throughout regional Western Australia Breastfeeding is the normal and safest way to nurture an infant, and prolonged exclusive breastfeeding duration of at least six months will yield the greatest gains in optimum infant development. Despite this knowledge breastfeeding rates in Australia plummet in the postpartum period with approximately 20% of babies no longer being exclusively breastfed after one week and less than this experiencing full breastfeeding at six months. Breastfeeding duration at four and six months is currently one of the Commonwealth’s category two indicators for the progress of chronic disease, however there is limited data on regional breastfeeding rates against which comparisons can be made. Breastfeeding initiation is almost universal and what is required are interventions that promote extended duration of any or exclusive breastfeeding. Providing social, professional and lay support for women to breastfeed is important and the availability of social support is a predictive factor in both initiating and sustaining breastfeeding. Women requiring breastfeeding assistance who live in regional Australia are often challenged by the limited availability of support services and lack of family and social support networks. The opportunities for the sharing of breastfeeding knowledge are diminished with the tyranny of distance.With the advent of the Internet has been the development of many varied e-Health interventions. The use of the Internet to deliver breastfeeding information is not new, however the incorporation of Webinars, chat rooms, Web cameras and discussion forums has taken the use of the Internet to support breastfeeding to a new level. In effect a virtual community can be created in a real and isolated geographical area. This research uses a Website intervention to support breastfeeding mothers and was initially implemented in the Midwest Region of Western Australia. A success of the research has been the adoption and adaption of this intervention by other regional dieticians working state wide. Mothers recruited to the study are randomised to receive the Internet intervention or normal services already available. The primary outcome of the research is to determine the effectiveness of the intervention in supporting breastfeeding duration. Data is collected longitudinally for a 12 month period. An overarching outcome from the research will be the collection of robust regional breastfeeding data that uses nationally agreed breastfeeding definitions. This presentation will present preliminary key findings from the research. It will provide much needed contemporary regional breastfeeding data required to help support the policy recommendation that WA health services become recognised as baby friendly institutes.